Imobilização de frutosiltransferase extracelular de Aspergillus oryzae IPT-301 em polihidroxibutirato e sua caracterização bioquímica para a produção de frutooligossacarídeos - Araújo, Isabella Medeiros (2021)
Fructooligosaccharides (FOS) refer to fructose oligomers, in which the fructosyl units are bound in β (2→1) position of sucrose, which distinguiches them other oligomers. The FOS, also known as “unconventional sugars”, present excellent functional characteristics in foods, beyound their physical and physiological aspects. These sugars can be produced about naturally, by enzymes, present in vegetables, or by microbial enzymes, such as fructosyltransferase (FTase, E.C.2.4.1.9), generated by Aspergillus oryzae IPT-301, which are the biocatalyst in transfructosylation reaction of sucrose. In that context, the current work focus on the studies of the immobilization process of the enzyme extracellular microbial FTase, using polyhydroxybutyrate as support, in the forms pure and functionalized, for the production of FOS. For this purpose, immobilization tests were performed, by physical adsorption and covalent bond, at temperature 35 ° C, for 8 hours, with agitation of 175 rpm, 10 mL fermented broth, pH 5.5, containing the extracellular microbial enzyme, and 1.0 g of support, pure and functionalized. For the characterization studies of the immobilized biocatalyst, it was made assays of the: incubation pH stability (4,0; 4,5; 5,0; 5,5; 6,0; 6,5 e 7,0), thermal stability (30 ºC, 40 ºC, 50 ºC e 60 ºC), assessment of the substrate concentration in the enzymatic reaction (200 g L-1, 300 g L-1, 400 g L-1, 470 g L-1, 500 g L-1 e 600 g L-1), operational stability and storage stability. The kinetic immobilization profiles indicated that the transfructosylation activity (), present in the fermented broth, decreased with the increase of the immobilization time and that the highest immobilization yield was about 41 ± 6 % for the adsorbed FTase in pure support and 55 ± 4 % for the immobilized FTase in funcionalized support. Besides these, it was discovered values of 17 ± 3 % and 11 ± 2 % for recovered activities for the immobilized enzyme in pure and functionalized supports, respectively. Thus, the conditions of the imobilization was definded for both support forms: temperature of 35 ºC, pH 5,5, stirring of 175 rpm and 8 h of immobilization. The highest values of were obtained for a sucrose concentration of 400 g L-1 for immobilized FTase in pure PHB and functionalized and the Hill model was fitted for immobilized FTase data from both supports. The immobilized enzyme in functionalized PHB presented higher thermal, operational, and storage stability than immobilized FTase in pure PHB. The immobilized FTase in functionalized PHB presented activity retention of 56,83 ± 4,38 % after six batch cicles, whereas absorbed enzyme in pure PHB presented activity retention of 41,29 ± 3,24 % of the initial activity. Thus, from the studies of the immobilization and characterization it was possible to conclude that the extracellular FTase was properly adsorbed in pure and functionalized PHB, presenting better results for the enzyme linked to functionalized biopolymer.